Pojęcie i pomiar efektywności - studia literaturowe - Kisielewska, Magdalena; Kozuń-Cieślak, Grażyna (Efficiency - the Concept and Measurement Issues, 2007)
The paper provides basics of the efficiency concepts and measurement. The evolution of the approaches in defining efficiency comes along with developing measures applied in efficiency evaluation. Researchers and practitioners are given a range of tools though from financial indicators to specific techniques such as Balanced Scorecard and frontier analyses.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 295-303